The Effect of Compensation, Work Discipline, and Motivation on Work Productivity at PT Pos Regional Division 1 - Iskandar, Dani; Aulia, Yunisa (Economic: Journal Economic and Business, 2023)
The purpose of this study was to determine and analyze compensation, work discipline, and motivation that have an indirect effect on work productivity at PT Pos Division Region 1 Medan, this research will be conducted through quantitative research methods with an associative approach. This research is located at PT. Medan Regional Division 1 Post, Jl. Prof. HM. Yamin Sh, Sei Kera Hilir II, Kec. Medan Perjuangan, Medan City, the population of this study are all employees of PT. The Medan Regional Division 1 post has a total of 85 employees, the sample used is a saturated sample where all the population is taken as a sample, namely 85 people. The data analysis technique used in this study is multiple linear regression analysis. The results of this study are that the Compensation Variable has a positive and significant effect on. Productivity because the value t hitung (3.086) > t tabel (1.988) and significance (0.016) < 0.05. The Discipline variable has a positive and significant effect on POS Employee Productivity because the value is t hitung (3.451) > t tabel (1.988) and the significance is (0.001) <0.05. The motivation variable has a positive and significant effect on POS Employee Productivity because the value thtung (3.337) > t tabel (1.988) and significance (0.002) < 0.05. Simultaneously both compensation, discipline and motivation have a positive and significant effect on POS Employee Productivity because F hitung (19.633) > F tabel (2.72) and significance (0.000) < ? (0.05) and the R Square value is 61.1% percent